Perfil epidemiológico da violência contra idosos a partir de ocorrências policiais - Andrade, Michele da Conceição [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The aim of this study was to verify the profile of occurrence of physical, psychological and sexual abuses and negligence against the elderly. It were analyzed the police occurrences of Defense of Woman Police from a city of São Paulo State during two years, about aggression: local, cause, relation victim:aggressor, presence of drug during aggression, social and demographic characteristics of aggressors and victims, the search of health services and medical reports by victims. It were used Fisher's Test and Chi-squared Test with p set at <0.05, to analyze the 201 cases. Among performed complaints, the major part of aggressors were men (66.2%) with white skin (54.7%) and the victims were women (95.5%), white (70.6%). There was higher prevalence of psychological abuse (51.7%) and the home (81.6%) was the most frequent local for aggressions. In larger part of cases, the aggressor was some relatives of victim (36.7%) and the cause was related to discussions (62.2%). There was low frequency of drug use (8.5%) and alcohol (15.4%) during violence. The majority of victims didn't search of medical help (67.2%). Among suffered lesions, it was more prevalent those that had mild level (89.3%) in area of upper limbs (38.5%) followed by head and neck (30.8%). It was concluded that the majority of abuses occurred at home by closed relatives, related to psychological violence

Objetivou-se nesse estudo verificar o perfil da ocorrência de maus-tratos físicos, psicológicos, sexuais e negligência contra idosos. Foram analisadas as ocorrências policiais da Delegacia de Defesa da Mulher de um município paulista, no período de dois anos, relativos à agressão: local; motivo; relação vítima-agressor; presença de drogas durante a agressão; características sociodemográficas de agressores e vítimas; procura das vítimas por serviço de saúde e o laudo médico. Foram utilizados teste de Fisher e Qui-quadrado com nível de significância p<0,05, para a análise dos 201 casos. Dentre as denúncias feitas, a maior parte dos agressores eram homens (66,2%) com pele branca (54,7%) e as vítimas mulheres (95,5%), brancas (70,6%). Houve maior prevalência de violência psicológica (51,7%) sendo a residência (81,6%) o local de maior frequência de agressões. Na maior parte dos casos o agressor era algum familiar da vitima (36,7%) e o motivo relacionado à discussões (62,2%). Houve baixa frequência do uso drogas (8,5%) e álcool (15,4%) durante os atos violentos. A maioria das vítimas não procurou por ajuda médica (67,2%). Dentre as lesões sofridas prevaleceu a de natureza leve (89,3%) na região de membros superiores (38,5%) seguida de cabeça e pescoço (30,8%). Conclui-se que a maioria das agressões ocorreu nos lares por parentes próximos, relacionadas à violência psicológica
Keywords: Violência familiar; Idosos; Saúde pública; Maus-tratos ao idoso; Family violence